STRATEGI MANAJEMEN VAKSIN EFEKTIF DI KOTA AMBON - Yustina Letty; Risky Kusuma Hartono; Semoel Leonard Samsu (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
Effective vaccine management is a critical component in the success of immunization programs, particularly in maintaining vaccine quality and ensuring availability at healthcare facilities. This study aims to analyze effective vaccine management strategies in Ambon City using the CIPP (Context, Input, Process, Product) evaluation approach. A qualitative method was employed, with data collected through in-depth interviews, observations, and document reviews involving 22 informants, including heads of primary healthcare centers, immunization program managers, vaccine managers, as well as representatives from the Health Office and the Pharmaceutical Installation Unit (UPTD). The findings indicate that, in terms of context, vaccine management is supported by national policies and directives from the Health Office, although no specific operational policies exist at the primary healthcare level. In the input aspect, human resources and infrastructure are relatively adequate; however, multiple job responsibilities and the lack of continuous training remain challenges. In the process aspect, vaccine distribution, storage, and temperature monitoring have been implemented according to standards, including the application of the FEFO principle and the use of Vaccine Vial Monitors (VVM), although the utilization of temperature monitoring technology is not yet optimal. In the product aspect, vaccine quality is well maintained with no significant damage reported; however, immunization coverage is still affected by distribution constraints and stock availability. In conclusion, vaccine management strategies in Ambon City have been operationally effective but require further strengthening through the standardization of local policies, enhancement of human resource capacity, and optimization of technology-based monitoring and distribution systems to improve sustainability and immunization program coverage. ABSTRAK Manajemen vaksin yang efektif merupakan komponen penting dalam keberhasilan program imunisasi, terutama dalam menjaga mutu vaksin dan menjamin ketersediaannya di fasilitas pelayanan kesehatan. Penelitian ini bertujuan untuk menganalisis strategi manajemen vaksin yang efektif di Kota Ambon menggunakan pendekatan evaluasi CIPP (Context, Input, Process, Product). Metode yang digunakan adalah kualitatif dengan teknik pengumpulan data melalui wawancara mendalam, observasi, dan telaah dokumen terhadap 22 informan yang terdiri dari kepala puskesmas, pengelola imunisasi, pengelola vaksin, serta pihak Dinas Kesehatan dan UPTD Farmasi. Hasil penelitian menunjukkan bahwa secara konteks, manajemen vaksin telah didukung oleh kebijakan nasional dan arahan Dinas Kesehatan, meskipun belum terdapat kebijakan operasional khusus di tingkat puskesmas. Pada aspek input, sumber daya manusia dan sarana prasarana relatif memadai, namun masih terdapat beban kerja rangkap dan pelatihan yang belum berkelanjutan. Pada aspek proses, distribusi, penyimpanan, dan pemantauan suhu vaksin telah berjalan sesuai standar dengan penerapan prinsip FEFO dan penggunaan VVM, meskipun pemanfaatan teknologi pemantauan suhu belum optimal. Pada aspek produk, mutu vaksin terjaga dengan baik dan tidak ditemukan kerusakan signifikan, namun capaian imunisasi masih dipengaruhi oleh kendala distribusi dan ketersediaan stok. Kesimpulannya, strategi manajemen vaksin di Kota Ambon telah berjalan efektif secara operasional, tetapi memerlukan penguatan melalui standarisasi kebijakan daerah, peningkatan kapasitas SDM, serta optimalisasi sistem pemantauan dan distribusi berbasis teknologi untuk meningkatkan keberlanjutan dan capaian program imunisasi.